Expression of intron-containing C. elegans heat shock genes in mouse cells demonstrates divergence of 3' splice site recognition sequences between nematodes and vertebrates, and an inhibitory effect of heat shock on the mammalian splicing apparatus. - Kay, R J (1987)
Splicing of a pair of intron-containing heat shock genes from Caenorhabditis elegans has been studied in transfected mouse cells. The hsp16-1 and hsp16-48 genes of C. elegans encode 16,000 Da heat shock polypeptides. Each gene contains a short intron of 52 (hsp16-1) or 55 (hsp16-48) base pairs. When these genes were introduced into mouse cells, they were efficiently induced following heat shock, but splicing of the introns was abnormal. In mouse cells, cleavage of the hsp16 transcripts occurred at the correct 5' splice sites, but the 3' splice sites were located at AG dinucleotides downstream of the correct sites. This aberrant splicing was not solely due to the small size of the C. elegans introns, since a hsp16-1 gene containing an intron enlarged by tandem duplication showed exactly the same splicing pattern. The mouse cells thus seem to be unable to recognize the natural 3' splice sites of the C. elegans transcripts. The efficiency of splicing was greatly reduced under heat shock conditions, and unspliced transcripts accumulated in the nucleus. During a subsequent recovery period at 37 degrees C, these transcripts were spliced and transported to the cytoplasm.